2021
DOI: 10.1080/02656736.2021.1874063
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided transvaginal radiofrequency ablation combined with levonorgestrel-releasing intrauterine system for symptomatic uterine adenomyosis treatment

Abstract: Objective: To evaluate the clinical outcomes of transvaginal ultrasound-guided radiofrequency ablation (RFA) combined with a levonorgestrel-releasing intrauterine system (LNG-IUS) for the treatment of symptomatic uterine adenomyosis. Methods: Patients with symptomatic uterine adenomyosis treated with ultrasound-guided RFA in combined with an LNG-IUS from January 2013 to January 2016 and followed up for 3 years after treatment were selected. Assessment endpoints included the uterine volume reduction rate, dysme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Forty-two articles were deemed eligible for inclusion in this meta-analysis. Included articles were composed of 14 studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20] regarding adenomyomectomy, 16 studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] regarding UAE, and 12 studies [37][38][39][40][41][42][43][44][45][46][47][48] regarding image-guided thermal ablation (HIFU nine studies, [37][38][39][40][41][42][43][44]…”
Section: Resultsmentioning
confidence: 99%
“…Forty-two articles were deemed eligible for inclusion in this meta-analysis. Included articles were composed of 14 studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20] regarding adenomyomectomy, 16 studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] regarding UAE, and 12 studies [37][38][39][40][41][42][43][44][45][46][47][48] regarding image-guided thermal ablation (HIFU nine studies, [37][38][39][40][41][42][43][44]…”
Section: Resultsmentioning
confidence: 99%
“…reported that when the distance from the ablative margin to the endometrium was at least 3 mm, the incidence rate of vaginal discharge after ablation was 33.3%. 40 While the safe distance between the ablative margin was not mentioned at all in some other studies, 7 , 8 , 9 , 36 , 37 , 38 , 41 , 42 it might contribute to the significant variance of the incidence rate of vaginal discharge. Overall, the non-unified standard of terminating the ablation procedure may contribute to the significant difference in the clinical outcomes of patients in different studies.…”
Section: Us-guided Mwa Proceduresmentioning
confidence: 95%
“…However, the termination criteria adopted in previous studies were not uniform, and individual research centers implemented their own standards. Different versions that can be observed include “the hyperechoic cloud covered the entire lesion”, 36 “80–90% of the entire lesion”, 37 , 38 “3–5 mm from the margin of the lesion”, 6 , 7 , 9 and “reached 0.3 cm to the serosa inferior margin or covered more than 1/2 of the lesion range”. 39 To prevent potential thermal damage to the adjacent organs, it is recommended that the distance from the ablative margin to the serosal surface should be at least 3 mm, which is one of the safety boundary standards for ablation of adenomyosis.…”
Section: Us-guided Mwa Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiofrequency ablation was also shown to maintain fertility with a pregnancy success rate reaching up to 50% making it a desirable option for patients who wish to conceive [ 75 ]. Radiofrequency ablation is also effective when combined with LNG-IUD demonstrated by a reduction of uterine volume and a decrease in dysmenorrhea [ 76 ].…”
Section: Resltsmentioning
confidence: 99%